Tendencia natural y libre en el pensamiento de Santo Tomás de Aquino - Ponce, Manuel Ocampo (Sapientia, 2013)
In the thought of St. Thomas Aquinas, both ethics and moral theology have as their central concept the concept of «the good», that is, of being insofar as it is desirable and insofar as it is the end of appetitive tendencies. This is due to the fact that the good expresses being insofar as it relates to the appetite, and thus it expresses the capacity of being to move the will, or of any tendency towards its end. For this reason St. Thomas holds with Aristotle that the good is convertible with the notion of end. And it is due to the importance of these principles and their consequences for morality and moral freedom that in this brief work I attempt to delve into the relationships between the good, the end, and nature, and some of its applications to what is known as natural tendency or natural appetite as well as to the free tendency which is called «the will», especially the will of the human person. It is not an attempt to present all the conclusions that follow from these principles—a task that would correspond to ethics or to moral theology—but an attempt to delve into the metaphysical principles that ground the moral order.